First record of the megamouth shark, Megachasma pelagios, (Chondrichthyes: Lamniformes: Megachasmidae) from Sri Lanka, northern Indian Ocean. (20th May 2015) - Fernando, Daniel; Perera, Nishan; Ebert, David A.
Abstract : The megamouth shark, Megachasma pelagios, is a rare and poorly studied shark. In this paper, the first record of the megamouth shark is reported for Sri Lanka. The shark, a juvenile estimated at 180 cm in total length, was caught in a gillnet in close proximity (<92 km) to the Negombo fisheries harbour (7°12′11.67″N 79°49′44.35″E).